Psychrometric Performance of the Air Dehumidifier Base Clothes Dryer - Wibowo Kusbandono; A. Prasetyadi; Nico Ndaru Pratama; Doddy Purwadianto; Rines; Y. B. Lukiyanto; I. G. K. Puja; Michael Seen; Budi Setyahandana (International Journal of Applied Sciences and Smart Technologies, 2026)
Drying clothes with dehumidifier machine and additional IR light experiments were conducted to show the psychrometric performance of dehumidification drying. Experiment of dehumidification drying 7.07 kg wet clothes to 4,78 kg dry clothes and 9.9 kg wet clothes to 7.67 kg dry clothes were applied. Variation of 715 W dehumidifier and 375 W IR were conducted. Measurement of room and environment temperatures and humidity were performed. The results show that additional IR make the drying process faster. However, it reduces drying effectivity. The efficiencies of drying are 109%, 96%, 100%, and 79% for drying 4.78 kg dry clothes with dehumidifier, drying 4.78 kg dry clothes with dehumidifier + IR, drying 7.67 kg dry clothes with dehumidifier, and drying 7.67 kg dry clothes with dehumidifier + IR. The numbers also reveal need of adopting drying COP using closed loop heat pump dehumidification to be ratio of heating and cooling energy over the supplied energy plus one.